American bison: Relic symbol? Domesticated novelty? Rewilding dream? - Benson, D. E., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The US Congress and President unanimously agreed on a national mammalian symbol with the National Bison Legacy Act of 2016. The law is entirely symbolic and could mean nothing to socially and ecologically rewild bison which might have totaled 30-60 million: the last clause of the bill reads "Nothing in this act or the adoption of the North American bison as the national mammal of the United States shall be construed or used as a reason to alter, change, modify, or otherwise affect any plan, policy, management decision, regulation, or other action by the federal government." Approximately 500,000 bison (20,000 plains and 10,000 wood bison) live in 62 conservation herds in the Great Plains and boreal forests of North America. Perhaps 15,000 bison are free-ranging and able to function ecologically. Relic extant populations persisted since near extirpation during the 1800s in Yellowstone National Park (4,900), and were restored on other public lands. Most numbers, 90 percent, were introduced to fenced private and tribal lands, bred for meat, husbanded as novelties and exhibits, or fostered for ecological and social considerations. The rewilding dream is limited by human populations and infrastructures, land uses, fragmented suitable landscapes, and attitudes that are incompatible with free-roaming wild herds of 1/2 to one ton ungulates. Mangers with governments, tribes, organizations, and private lands seek uncertain futures for bison considering legislation, land use alternatives, economics, social perspectives, dreams, and actions that not all can agree. Must we accept symbolic management of relics or ecologically rewild our dreams.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.